Fabrication and spray-drying microencapsulation of vitamin C-loaded W1/O/W2 emulsions: Influence of gel polymers in the internal water phase on encapsulation efficiency, reconstituted stability, and controlled release properties. (1st December 2022) - Hu, Shihong; Ding, Zhuang; Zhang, Gang; Wang, Xiao; Zhao, Yanna; Fan, Zhiping; Liu, Min; Han, Jun; Wang, Zhengping
Abstract: Water-in-oil-in-water (W1 /O/W2 ) emulsions represent promising multilayer encapsulation systems for protecting hydrophilic nutraceutical and pharmaceutical components. However, the strong leakage of hydrophilic components from W1 to W2 limits the practical applications of these emulsions. The purpose of this study was to investigate the influence of gel polymers present in W1 on the performance characteristics of W1 /O/W2 emulsions and their derived microencapsulated powders. Herein, cationic polymer chitosan and nonionic polymer hydroxypropylmethylcellulose (HPMC) were used as gelling agents in W1 to produce vitamin C (VitC)-loaded W1 /O/W2 emulsions and the corresponding spray-dried microcapsules. A sample containing low viscosity chitosan possessed the highest encapsulation efficiency (91.9%), and its derived microcapsules exhibited an almost completely reconstituted microstructure and high encapsulation stability (80.8%) after rehydration. In contrast, two formulations containing HPMC produced a negative impact on these critical parameters. Importantly, VitC was effectively retained in W1, as indicated by its electrostatic conjugation with chitosan and increased viscosity. This study demonstrated that the selection of appropriate gel polymers for W1 is an effective strategy for enhancing the encapsulation performance of W1 /O/W2 emulsions and commercial production of the corresponding dried microcapsules. Graphical abstract: Image 1 Highlights: Vitamin C-loaded W1 /O/W2 emulsions and their dry microcapsules are prepared. Chitosan and hydroxypropylmethylcellulose (HPMC) are used as gelling agents. A sample with low viscosity chitosan exhibits the highest encapsulation efficiency. VitC was retained in W1 mainly due to its electrostatic bonding with chitosan. HPMC addition produces a negative impact on encapsulation stability.